The role of precautions: Organising a medical conference during COVID‐19 pandemic-Lessons from IADVL MIDDERMACON 2021 - Ramesh Bhat; Suvidha D. Kamath; Nicole Sequeira; Sunil Raina; Ganesh S. Pai; Dandakeri Sukumar; Jacintha Martis (Wiley, 2022)
Abstract Background The use of virtual platforms for clinical meetings has become the default approach during this pandemic era. Organising an offline conference during a pandemic is a challenge and is possible if the participating crowd is vaccinated and is willing to follow appropriate pandemic protocols. Objective To determine the feasibility of conducting a conference among mostly vaccinated delegates using standard precautionary protocols. Methods This study was conducted at IADVL MIDDERMACON 2021, held in Mangalore, India, in late October 2021, during the phase of decline of the Delta variant of SARS‐CoV‐2. The study population included all conference attendees, including support staff. Details were collected about their vaccination status, comorbidities, and mode of travel to the conference venue. An reverse‐transcription polymerase chain reaction (RT‐PCR) test was done randomly among the attendees for COVID‐19 infection. A post‐conference assessment and RT‐PCR tests were done at the end of 2 weeks to assess the occurrence of infections among study participants. Results A total of 1744 people were present at the venue, of which 576 (33.03%) participated in the study. The percentage of fully vaccinated was 88.88% (512/576). The majority had taken the vaccine Covishield (manufactured by AstraZeneca), that is, 85.06% (490/576). Infection post the conference was reported in 0.195% (1/576). Conclusions Holding large gatherings like medical conferences pose a challenge during a pandemic. However, to increase the benefits of the conference, it is advisable to hold them offline with vaccinated delegates, follow the advice of the conference organising committee, and practise safe precautionary measures.